2017
DOI: 10.1016/j.ijheatmasstransfer.2016.12.071
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clustering role versus Brownian motion effect on the heat conduction in nanofluids: A novel approach

Abstract: In this study, the temperature and viscosity-dependent methods were used to identify the main heat conduction mechanism in nanofluids. Three sets of experiments were conductedto investigate the effects of Brownian motion and aggregation. Image processing approach was used to identify detailed configurations of different nanofluids microstructures. The thermal conductivity of the nanofluids was measured with respect to the dynamic viscosity in the temperature range between 0 and 55 °C. TheResultsclearly indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Daviran et al reported the effect of temperature to play role in the enhancement of effective thermal conductivity which not necessarily due to increased Brownian motion but may also result in formation of clusters due to collision. 49 The dependence of both these phenomena (temperature and clustering) are depicted in Figure 8, illustrating the key contribution of particle aggregation for the enhanced heat transfer of these nanofluids at high concentrations and temperatures.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Daviran et al reported the effect of temperature to play role in the enhancement of effective thermal conductivity which not necessarily due to increased Brownian motion but may also result in formation of clusters due to collision. 49 The dependence of both these phenomena (temperature and clustering) are depicted in Figure 8, illustrating the key contribution of particle aggregation for the enhanced heat transfer of these nanofluids at high concentrations and temperatures.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Daviran et al [57] studied the effect of clustering and Brownian motion effect on the thermal conductivity of the nanofluid. It has been reported that Brownian motion does not play a significant role in thermal conductivity of nanofluid.…”
Section: Lee Etmentioning
confidence: 99%
“…The Brownian motion also affects the thermal conductivity of nanofluids. The motion of nanoparticles itself and convection caused by Brownian motion will obviously improve the thermal conductivity [123][124][125]. Nanofluid as a new type of insulating material for transformers is a new development prospect to traditional oil-paper insulation system.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…The Brownian motion also affects the thermal conductivity of nanofluids. The motion of nanoparticles itself and convection caused by Brownian motion will obviously improve the thermal conductivity [123–125].…”
Section: Thermal Conductivitymentioning
confidence: 99%